Land use & environment law review. - Strom, Frederic A. (New York Clark Boardman, 1997)
Annual.
Editor: 1978- F.A. Strom.
Keywords: Environmental law -- United States -- Periodicals; Land use -- United States -- Law and legislation -- Periodicals